Study on The Installation of Urea Synthesis Tower Using Hoisting Structure Based On Truss Support - Won IK Jun; Jang Yong Su (Talenta Publisher, 2025)
The paper addresses the scientific and technological issues of securing the installation of heavy objects, including urea synthesis towers, on a building with limited erecting area using hoisting structure based on truss support.